(untitled) - Lewin, Mathieu (Comptes Rendus. Physique)
I present some open mathematical problems concerning electrons in quantum mechanics and charged particles in general. After discussing the Schrödinger Hamiltonian describing atoms and molecules with classical nuclei, I turn to infinite systems and in particular to the homogeneous electron gas.